Pulmonary Artery Sarcoma - Maha Shomaf MD; Nathir Obeidat MD; Fatin Al-Fares MD; Saleh Najjar M.D (SAGE Publishing, 2014)
Pulmonary artery sarcomas (PAS) are extremely rare sarcomas of uncertain histogenesis that often mimic pulmonary thromboemboli. This is a report of a 60-year-old female patient who presented with recurrent chest pain and cough. The patient was first diagnosed with pulmonary embolism but she did not improve on anticoagulant therapy. Follow-up imaging studies revealed a mass in the left hilar region extending into the pulmonary trunk and branches of the left pulmonary artery. The tru-cut biopsy revealed an undifferentiated sarcoma. The patient died 10 months after her initial presentation.